'Dear God, I am not a son of a bitch': Justifications for patriarchal violence and the mischaracterization of Stephen King's Jack Torrance. Issue 2 (1st October 2021) - Stephens, Tracy A.
Stephen King has criticized Stanley Kubrick's adaptation of The Shining for its characterization of Jack Torrance as an unsympathetic monster rather than a well-intentioned man tragically destroyed by his addiction and anger. However, a re-examination of the novel and its sequel shows that King's Jack Torrance is, no matter what King says, a dangerous patriarchal figure long before he enters the Overlook. The Shining and Doctor Sleep detail Jack's wife and son's co-dependent attachment to him, their wariness and fear of him, his long history of toxic behaviour and his deep capacity for self-deception that all help to expose a justifying narrative for patriarchal violence. However, King's extratextual defences of Jack and the critical narrative that reaffirms his assessment of Jack's moral character must be part of our analysis of The Shining's critique of patriarchal ideology, as the contrast between those statements and the textual evidence reveal a desire to see Jack as sympathetic that makes King and the audience complicit in the same narrative of justification that the novel exposes.